Life-cycle health effects of compulsory schooling - Hollenbach, Johannes; Schmitz, Hendrik; Tawiah, Beatrice Baaba (The European Journal of Health Economics)
Abstract We study the effect of education on health (hospital stays, number of diagnosed conditions, poor or bad self-rated health, and body mass index) over the life cycle, using German compulsory schooling reforms as a source of exogenous variation. Our results show clear correlations between educational attainment and better health across all age groups (30 to 74). However, we do not find causal relationships between additional schooling and health or health care utilization, neither earlier nor later in life. A simulated ex-post power analysis shows that this is not due to a lack of statistical power. One reason for the absence of effects may be that the studied compulsory schooling reforms succeeded in raising the educational attainment of the target group - individuals at the lowest educational margin - but did not lead to healthier employment opportunities.

Gene-environment interactions with essential heterogeneity - Hollenbach, Johannes; Schmitz, Hendrik; Westphal, Matthias (The Economic Journal)
Abstract We study how gene-environment interactions between education and genetic endowments affect cognition in old age and use this setting to show that – even with a valid instrument – two-stage least squares (2SLS) estimates of interaction effects can be far away from the true effect. This is the case when treatment effects are heterogeneous and compliance to the instrument depends on the interaction variable. We suggest estimating marginal treatment effects to address this problem. Our estimation results show complementarities between education and genetic predisposition in determining later-life memory. The marginal treatment effect estimates suggest substantially larger gene-environment interactions than the 2SLS estimates.

Bildung in der Jugend hält das Gehirn jung - Schmitz, Hendrik; Matthias, Westphal (Wirtschaftspsychologie heute)

Education as a Moderator of Genetic Mortality Risk - Schmitz, Hendrik; Nguyen, Thao Le

The Effect of Compulsory Schooling on Vaccination Against COVID - Monsees, Daniel; Schmitz, Hendrik (Health Economics)
ABSTRACT We study the effect of education on vaccination against COVID in Germany in a sample of individuals above the age of 60. In ordinary least squares regressions, we find that, in this age group, one more year of education goes along with a 0.7 percentage point increase in the likelihood to get a COVID vaccination. In two stage least squares regressions where changes in compulsory schooling laws are used as exogenous variation for education, the effect of an additional year of education is estimated to be zero. The results hold for the compliers to the policy change which are older individuals at the lowest margin of education.

Science knowledge localizes - Balsmeier, B.; Lück, Sonja; Fleming, L. (Research Policy)

Prudence and prevention – empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics Letters)

Early- and Later-Life Stimulation: How Retirement Shapes The Effect of Education on Old-Age Cognitive Abilities - Schmitz, Hendrik; Westphal, Matthias

The Effects of Norms on Environmental Behavior - Dannenberg, Astrid; Gutsche, Gunnar; Batzke, Marlene C. L.; Christens, Sven; Engler, Daniel; Mankat, Fabian; Möller, Sophia; Weingärtner, Eva; Ernst, Andreas; Lumkowsky, Marcel; von Wangenheim, Georg; Hornung, Gerrit; et al. (Review of Environmental Economics and Policy)

The individual and ecological characteristics of parental COVID-19 vaccination decisions - Hörnig, Lukas; Schaffner, Sandra; Schmitz, Hendrik (Scientific Reports)
Abstract Vaccination is a highly effective method to prevent the spread of COVID-19 and mitigate severe disease. In Germany, adult vaccination rates are relatively high at 85.5%, but rates are significantly lower for adolescents (69.6%) and children (20.0%). This discrepancy indicates that not all vaccinated parents choose to vaccinate their children. Analyzing data from a January 2022 online survey of 1,819 parents with children and adolescents, we explore the socio-economic factors influencing parents’ willingness to vaccinate themselves and their children. Our results show that individuals who vote for either side of the political extremes are less likely to vaccinate their children. This pattern is particularly strong for voters on the far right. In addition, we find that better educated parents are more likely to vaccinate both themselves and their children. Parents who vaccinate both themselves and their children demonstrate greater confidence in the vaccine’s effectiveness, while those who vaccinate only themselves are often motivated by a desire to regain personal freedoms. These insights highlight the need for targeted public health strategies to address specific concerns and improve vaccination rates among children and adolescents.

Regional variations in vaccination against COVID-19 in Germany - Bade, Verena; Schmitz, Hendrik; Tawiah, Beatrice Baaba (PLOS ONE)
Vaccination willingness against COVID-19 is generally perceived as low. Moreover, there is large heterogeneity across and within countries. As a whole, Germany has average vaccination rates compared to other industrialized countries. However, vaccination rates in the 16 different German federal states differ by more than 20 percentage points. We describe variation in vaccination rates on the level of the 400 German counties using data on all vaccinations carried out until December 2022. Around 52-72% of that variation can be explained by regional differences in demographic characteristics, housing, education and political party preferences. We find indications that the remaining part may be due to differences in soft factors such as risk aversion, trust in the German government, trust in science, and beliefs in conspiracy theories regarding the origins of the Corona virus. We conclude that improving the trust in science and the fight against conspiracy theories may possibly be effective tools to improve vaccination rates and effectively fight pandemics.

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik (European Economic Review)
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England, and several countries in Continental Europe, we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance for cognitive functioning of maintaining good physical health in old age.

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Determinants of individual sustainable investment behavior - A framed field experiment - Gutsche, Gunnar; Wetzel, Heike; Ziegler, Andreas (Journal of Economic Behavior & Organization)

Does education have an impact on patience and risk willingness? - Tawiah, Beatrice Baaba (Applied Economics)

Late-Career Unemployment and Cognitive Abilities - Freise, Diana; Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)
We study the effect of unemployment on cognitive abilities among individuals aged between 50 and 65 in Europe. To this end, we exploit plant closures and use flexible event-study estimations together with an experimentally elicited measure of fluid intelligence, namely word recall. We find that, within a time period of around eight years after the event of unemployment, cognitive abilities only deteriorate marginally — the effects are insignificant both in statistical and economic terms. We do, however, find significant effects of late-career unemployment on the likelihood to leave the labor force, and short-term effects on mental health problems such as depression and sleep problems.